Surgical cause of respiratory distress in a newborn - M., Vishnu Vardhan Reddy; C., Suguna Reddy; Nagendhar, Yoga; D., Vardhini Sree (International Journal of Contemporary Pediatrics, 2021)
Common causes of respiratory distress in a term infant include transient tachypnoea of newborn, sepsis/congenital pneumonia and congenital heart diseases. Surgical causes of distress in a newborn are rare and should be considered when other causes have been ruled out. We report a case of an early term female neonate who developed respiratory distress immediately after birth which was gradually progressive and required respiratory support. On evaluation with chest radiography and CT, a diagnosis of congenital lobar emphysema (CLE) was made. Immediate surgical resection was planned and done on day 8 of life. Post operatively she had no respiratory distress and discharged within a week. Baby is now healthy with normal growth and development. Half of the cases of CLE are diagnosed within the first 6 months of life but very few cases present with respiratory distress since birth. Timely diagnosis and early surgical excision in neonates <2 months improve the outcome, as seen in our case.